Carpoglyphus lactis (Acari: Astigmata) from various dried fruits differed in associated micro-organisms - Hubert, J; Nesvorná, M; Kopecký, J; Ságová-Marečková, M; Poltronieri, P (Journal of applied microbiology, 2015)
AIMS: Carpoglyphus lactis is a stored product mite infesting saccharide-rich stored commodities including dried fruits, wine, beer, milk products, jams and honey. The association with micro-organisms can improve the survival of mites on dried fruits. METHODS AND RESULTS: The microbial communities associated with C. lactis were studied in specimens originating from the packages of dried apricot, plums and figs and compared to the laboratory strain reared on house dust mite diet (HDMd). Clone libraries of bacterial 16S rRNA gene and fungal internal transcribed spacer (ITS) region were constructed and analysed by operational taxonomic unit (OTU) approach. The 16S rRNA gene libraries differed among the compared diets. The sequences classified to the genera Leuconostoc, Elizabethkingia, Ewingella, Erwinia, Bacillus and Serratia were prevailing in mites sampled from the dried fruits. The ITS library showed smaller differences between the laboratory strain on HDMd and the isolates from dried fruits packages, with the exception of the mite strain from dried plums. The population growth was used as an indirect indicator of fitness and decreased in the order from yeast diet to HDMd and dried fruits. CONCLUSIONS: The treatment and pretreatment of mites by antibiotics did not reveal the presence of antagonistic bacteria which might slow down the C. lactis population growth. The shifts of the microbial community in the gut of C. lactis were induced by the diet changes. The identified yeasts and bacteria are suggested as the main food source of stored product mites on dried fruits. SIGNIFICANCE AND IMPACT OF THE STUDY: The study describes the adaptation of C. lactis to feeding on dried fruits including the interaction with micro-organisms. We also identified potentially pathogenic bacteria carried by the mites to dried fruits for human consumption.
Keywords: roztoči; packages; dried fruit; Fungi; Diet; Mites; houby; RNA ribozomální 16S; mite; antibakteriální látky; zvířata; RNA, Ribosomal, 16S; Anti-Bacterial Agents; dieta; feeding; ovoce; Bacillus; Fruit; infestation; Bacteria; Animals; fungi; bacteria; Gastrointestinal Tract; gastrointestinální trakt